Effects of Human Fibroblast-Derived Multi-Peptide Factors on the Proliferation and Migration of Nitrogen Plasma-Treated Human Dermal Fibroblasts - Lee SY; Kim DY; Suh SB; Suh JY; Cho SB (Dove Medical Press, 2022)
Song Yi Lee,1,* Do Yeon Kim,1,* Sang Bum Suh,1 Ji Youn Suh,1 Sung Bin Cho2 1BNV Biolab, Seoul, Korea; 2Yonsei Seran Dermatology and Laser Clinic, Seoul, Korea*These authors contributed equally to this workCorrespondence: Sung Bin Cho, Yonsei Seran Dermatology and Laser Clinic, 224 Siheung-daero, Seoul, 08628, Korea, Tel +82 2-2135-1375, Fax +82 70-8250-1375, Email drsbcho@gmail.comBackground: Human fibroblast-derived multi-peptide factors (MPFs) promote wound repair by playing crucial roles in cell recruitment, adhesion, attachment, migration, and proliferation.Methods: Cultured human dermal fibroblasts (HDFs) were directly treated with non-contact low- and high-energy nitrogen plasma and further cultured in various conditioned media. Cell proliferation and wound-healing properties were evaluated.Results: In Opti-modified Eagle's medium + GlutaMAX culture, reduced HDF viability was observed 24 h after 2-J/pulse plasma treatment and 12 and 24 h after 3-J/pulse treatment. Meanwhile, in dermal fibroblast-conditioned medium (DFCM) containing MPF culture, reduced HDF viability was observed only 24 h after 3-J/pulse treatment. Under DFCM-MPF culture, the wound area percentage was significantly decreased after 12 and 24 h in untreated HDFs; at 9, 12, and 24 h after 1-J/pulse plasma treatment; at 3, 6, 9, 12, and 24 h after 2-J/pulse plasma treatment; and at 9, 12, and 24 h after 3-J/pulse plasma treatment. Greater migration of HDFs with or without plasma treatment was found in DFCM-MPFs than in other conditioned media.Conclusion: Low-energy nitrogen plasma treatment promotes HDF proliferation and wound repair. DFCM-MPFs enhanced cell proliferation and improved the wound healing properties of HDFs treated with low- and high-energy plasma.Keywords: human dermal fibroblasts, multi-peptide factors, dermal fibroblast-conditioned media, plasma, nitrogen, cell proliferation, wound healing, cell migration